2020
DOI: 10.1021/acscombsci.0c00102
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Machine-Learning-Aided Screening of Hydrogen Adsorption on Bimetallic Nanoclusters

Abstract: Nanoclusters add an additional dimension in which to look for promising catalyst candidates, since catalytic activity of materials often changes at the nanoscale. However, the large search space of relevant atomic sites exacerbates the challenge for computational screening methods and requires the development of new techniques for efficient exploration. We present an automated workflow that systematically manages simulations from the generation of nanoclusters through the submission of production jobs, to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 65 publications
1
8
0
1
Order By: Relevance
“…[24b] Jiang et al have also showed that an adjusted coordination number can act as a general descriptor to bridge the structure and reactivity for the oxygen sites over transitionmetal oxides. [25] In addition, if the properties are derived from electron density, [26] they are referred to as electronic descriptors. These descriptors are usually obtained from electronic structure calculations, which are time-consuming owing to the first principles/ab initio calculations required.…”
Section: Descriptors For Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[24b] Jiang et al have also showed that an adjusted coordination number can act as a general descriptor to bridge the structure and reactivity for the oxygen sites over transitionmetal oxides. [25] In addition, if the properties are derived from electron density, [26] they are referred to as electronic descriptors. These descriptors are usually obtained from electronic structure calculations, which are time-consuming owing to the first principles/ab initio calculations required.…”
Section: Descriptors For Electrocatalysismentioning
confidence: 99%
“…In addition, if the properties are derived from electron density, [ 26 ] they are referred to as electronic descriptors. These descriptors are usually obtained from electronic structure calculations, which are time‐consuming owing to the first principles/ab initio calculations required.…”
Section: Descriptors For Electrocatalysismentioning
confidence: 99%
“…This will likely require development of the descriptor used in the training process, taking into account a more detailed description of the local chemical character than offered by the elemental name alone. 70,71…”
mentioning
confidence: 99%
“…Manifold learning algorithms generate low-dimensional representations that retain neighborhood relationships in the original high-dimensional data, allowing visualization and modeling (Figure ). , The t-distributed stochastic neighbor embedding (t-SNE) algorithm has been used extensively for the visualization of high-dimensional data in two or three dimensions. ,, However, the large time complexity of this algorithm, and variations in data visualizations that are highly dependent on the selection of hyperparameters, limit its applications. An improved algorithm, uniform manifold approximation and projection (UMAP) is an efficient dimensional reduction technique for data visualization and nonlinear dimension reduction .…”
Section: Machine Learning Modelingmentioning
confidence: 99%